Driving corporate climate transparency: The role of financial distress, environmental performance, and executive incentives - Rahayu, Hanif Yulinar Tri; Widyastuti, Aviani; Harventy, Gina (Universitas Muhammadiyah Malang, 2026)
Purpose: This study aims to test and empirically analyze the effect of financial distress, environmental performance, and executive compensation on greenhouse gas emission disclosure. Method: The population in this study was 4 company sectors listed on the Indonesia Stock Exchange (IDX), with a sample of 113 companies listed on the Indonesia Stock Exchange (IDX) in 2021. The number of samples is determaind by the judgment sampling method. Hypothesis testing is done by STATA tools with multiple linear regression data analysis techniques. Findings: The results of this study show that financial distress is not statistically supported by greenhouse gas emission disclosure, while environmental performance and executive compensation have a significant effect on greenhouse gas emission disclosure. Novelty: This research adds literature and provides new insights into the company's financial condition after the COVID-19 pandemic to voluntary disclosures, namely greenhouse gas emission disclosure. In addition, there are other variables, namely environmental performance and executive compensation for greenhouse gas emission disclosure. This research was also conducted in a sector that had never been done in previous studies.